Cooling performance of nanofluid submerged vs. nanofluid circulated battery thermal management systems. (10th December 2019) - Jilte, R.D.; Kumar, Ravinder; Ahmadi, Mohammad H.
Abstract: For a cleaner environment, the production of fossil fuel propelled transport vehicles need to reduce. Technological advances are aimed to manufacture cost-effective battery electric vehicles compared with the conventional one. An efficient battery cooling system is necessary for safer usage of electric cars during their life cycle. This paper presents two ways of arranging cooling components: liquid filled battery cooling systems (LfBS) and liquid circulated battery cooling systems (LcBS). The air conditioning unit of an electric vehicle has integrated with the battery cooling unit. Cooling performance of LfBS and LcBS arrangements presented for both water and nanofluid as cooling media at 2C and 4C discharge rates. The air required for LfBS cooling or LcBS cooling has supplied at two supply conditions: first, if the ambient temperature is around 35 °C and air-conditioning is 'OFF' in an electric vehicle. Second, air-conditioning is 'ON' and recirculated air from car cabin is available at 30 °C to supply it to the battery cooling system. The result shows the applicability of such battery systems for the safe operation of electric vehicles. Highlights: Cooling of the battery module with liquid filled and liquid circulated BTMS. Performance comparison based on water and nanofluid as cooling media. Ambient conditions and electric vehicle's air-conditioned supply air used. Applicability for each case is illustrated with analysis.